Characterization of iron(III)porphyrin-hydroxo complexes in organic media through UV-Vis and EPR spectroscopies - Manso, CMCP; Neri, C. R.; Vidoto, E. A.; Sacco, H. C.; Ciuffi, K. J.; Iwamoto, L. S.; Iamamoto, Y.; Nascimento, O. R.; Serra, O. A. (Elsevier B.V., 1999)
The interaction of OH- with Fe(TPP)(+), Fe(TDCPP)(+), Fe(TMP)(+) and Fe(TFPP)(+) in 1,2-dichloroethane was studied by titrating FeP solutions with aliquots of a solution of tetrabutylammonium hydroxide in acetonitrile. The number of OH- ions (n) coordinated to the FeP and the stability constants (beta(n)) for the FeP-OH- complexes were calculated from UV-Vis absorbance data and iron spin states were determined through EPR spectroscopy, Fe(TMP) (+) forms a high-spin mono-hydroxo complex, while Fe(TPP)I and Fe(TDCPP)(+) form high-spin bis-hydroxo complexes. To our knowledge, this is the first time that the formation of bis-hydroxo complexes from Fe(TPP) (+) has been reported, and this was possible because the studies were carried out in basic organic media, In this same medium, Fe-III-Fe-II reduction upon OH- addition to Fe(TFPP) (+) was observed, without concomitant formation of the mu-oxo dimeric species [Fe(TFPP)](2)O. (C) 1999 Elsevier B.V., All rights reserved.
Keywords: porphyrins; ironporphyrins; tetrabutylammonium hydroxide; titrations